Endemic fish diversity of Western Ghats - Ponniah, A. G. (NBFGR-NATP publ., 2000)
Papers presented at the Workshop on Germplasm Inventory and Genebanking of Freshwater Fishes, held at Central Marine Fisheries Research Institute, Cochin, India in 1998; organized by National Bureau of Fish Genetic Resources.